Comorbidity of Symptoms of Alcohol and Cannabis Use Disorders among a Population-Based Sample of Simultaneous Users. Insight from a Network Perspective - Baggio, Stéphanie (Int J Environ Res Public Health, 2018)
Research into comorbidity of alcohol and cannabis use disorders has resulted in inconsistent findings, especially among simultaneous users, who used alcohol and cannabis together on a single occasion. This study investigated the association of alcohol and cannabis use disorders among simultaneous users using a network perspective, which considers direct relationships between symptoms. We used a subset of simultaneous alcohol and cannabis users driven from the representative population-based sample of young Swiss men cohort study on substance use risk factors (C-SURF) (n = 1559 at baseline and n = 991 at follow-up). Self-reported symptoms of alcohol and cannabis use disorders were collected. Network analyses included network estimation, visualization, and community detection tests. Alcohol and cannabis use symptoms were separated in two distinct clusters, with few paths between them (eleven positive edges at baseline, three at follow-up). Withdrawal symptoms were likely to connect the two disorders at baseline, but not at follow-up. Alcohol and cannabis use disorders appeared as separate disorders among simultaneous users. Our findings mitigated previous findings on the detrimental association between alcohol and cannabis use. Future studies should incorporate network analyses as a means to study comorbidity in other community and clinical samples to confirm our preliminary findings.